Introduction to Materials Science for Engineers - Shackelford, James F. (New Delhi Pearson Education, 2007)
This book provides balanced, current treatment of the full spectrum of engineering materials, covering all the physical properties, applications and relevant properties associated with engineering materials. The book explores all of major categories of materials while offering detailed examinations of a wide range of new materials with high-tech applications. The reader is treated to state-of-the-art computer generated crystal structure illustrations, offering the most technically precise and visually realistic illustrations available. The book includes over 350 exercises with sample problems to provide guidance. Materials for Engineering, Atomic Bonding, Crystal Structure and Defects, Diffusion, Mechanical Behavior, Thermal Behavior, Failure Analysis & Prevention. Phase Diagrams, Heat Treatment, Metals, Ceramics and Glasses, Polymers, Composites, Electrical Behavior, Optical Behavior, Semiconductor Materials, Magnetic Materials, Environmental Degradation, Materials Science. For mechanical and civil engineers and machine designers.